The HLA‐A, ‐B and ‐DRB1 polymorphism in a large dataset of South Brazil bone marrow donors from Rio Grande do Sul. (2nd December 2016) - Boquett, J. A.; Nunes, J. M.; Buhler, S.; de Oliveira, M. Z.; Jobim, L. F.; Jobim, M.; Fagundes, N. J. R.; Schüler‐Faccini, L.; Sanchez‐Mazas, A.
Abstract: Human leukocyte antigen (HLA) genes are very informative in population genetics studies and their variability has been widely used to reconstruct the history of geographic and/or demographic expansions of human populations. The characterization of HLA diversity at the population level is also fundamental in clinical studies, particularly for bone marrow transplantation programs. In this study, we investigated the HLA molecular variation in Rio Grande do Sul, South Brazil, in order to identify possible regional differences across this state. More than 97, 000 bone marrow donors were typed at the HLA‐ A, ‐B and ‐DRB1 loci and analyzed by considering two kinds of subdivisions based on both self‐identified ethnicity and place of residence: (a) the official geographic subdivision defined by the Brazilian Institute of Geography and Statistics and (b) known information about the colonization history of the state. HLA allele and haplotype frequencies were estimated and compared among the defined subgroups. The results indicate a lack of correlation between genetic variation and geography and thus no clear HLA genetic structure based on geographic criteria. On the other hand, major differences were observed regarding ethnicity. In addition, local populations from Rio Grande do Sul were found to be genetically similar to their corresponding parental European populations from Germany, Italy and Portugal, as documented by historical data. Overall, this study provides a thorough characterization of the HLA genetic variation in Rio Grande do Sul and a better understanding of its demographic history, being most useful for the development of more efficient strategies in bone marrow donors' recruitment.